Aspects of Civil Law in Wedding Organizer Service Agreements with Installment Payments - Sri Rumada Sihite (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
Current developments have made various aspects of human life easier, one of which is asking other parties to take responsibility for managing all aspects of a wedding, known as a wedding organizer. However, wedding organizer agreements do not always run smoothly. There are many legal issues that arise from wedding organizer agreements, one of which is default, where the WO agreement does not match the agreement. This is what attracted the author to conduct research on wedding organizers, Research method: The type of research used is normative legal research using a state approach. The legal sources used are primary law, secondary legal materials, and tertiary law. Research results: It is explained that the civil law aspects of the legal subjects who enter into the agreement are competent and have fulfilled the elements of a valid agreement, namely agreement and legal protection for the users of wedding organizer services, namely that the party in breach of contract can refer to Articles 1243 and 1246 of the Civil Code, namely that if one party fails to fulfill its obligations in the agreement, it can claim compensation such as costs, compensation, and interest.